2015
DOI: 10.1016/j.bbamem.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the mitochondrial voltage dependent anion channel (VDAC) by curcumin

Abstract: Voltage dependent anion channel (VDAC) of mitochondria plays a crucial role in apoptosis. Human VDAC-1, reconstituted in planar lipid bilayer showed reduced conductance when treated with curcumin. Curcumin interacts with residues in the α helical N-terminus of VDAC and in the channel wall, as revealed by molecular docking, followed by mutational analysis. N-terminus mimicking peptide showed conformational changes in circular dichroism, upon curcumin treatment. We propose that the interaction of curcumin with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…Both modeling and artificial bilayer experiments revealed that the S193E variant opens and closes less frequently than does the wild-type [43] although the open state conductances are similar (3.7 and 3.9 nS, respectively, [44]). In this case, the N-terminal methionine is not present in the native form [45], but presumably remains in the recombinant one.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Both modeling and artificial bilayer experiments revealed that the S193E variant opens and closes less frequently than does the wild-type [43] although the open state conductances are similar (3.7 and 3.9 nS, respectively, [44]). In this case, the N-terminal methionine is not present in the native form [45], but presumably remains in the recombinant one.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Another drug in trials for cancer, the natural product curcumin, also has been shown to activate AMPK and inhibit mTOR (57)(58)(59). Interestingly, a recent study demonstrated that, similar to itraconazole, curcumin also interferes with VDAC1 function (60).…”
Section: Discussionmentioning
confidence: 99%
“…Results of a study by Scharstuhl et al [49] imply that VDAC is involved in fibroblast apoptosis induced by curcumin. Molecular docking followed by mutational analysis indicate that curcumin interacts with amino acid residues in the alpha helical N-terminus of VDAC and in the channel wall, thus restricting the movement of the helix by fixing it in a closed conformation [50]. Therefore, curcumin interferes with opening of the channel, as evidenced by a decrease in VDAC conductance upon treatment with the phenolic compound.…”
Section: Class IV Mitocans: Deregulators Of Vdac/ant Complexmentioning
confidence: 98%